COVID-19 Pandemic and Neonatal Health: What We Know so Far? - Bhandari, T.R.; Dangal, G. (Kathmandu University Medical Journal, 2020)
COVID-19 first time appeared in December 2019 in Wuhan, China. The number of cases increased rapidly in china and outside and the World Health Organization declared a pandemic on 11th March 2020. The pregnant and postpartum women, child, and neonatal populations are vulnerable to this disease due to immunological and physiological changes. This paper analyzed the published evidence for assessing the effect of COVID-19 on neonatal health and health care. Online published literature was searched from PubMed, Google Scholar, and other official webpages using keywords: “coronavirus/COVID-19/new coronavirus 2019”/SARS-CoV-2 and neonatal health/care/outcomes” and reviewed to prepare this article. COVID-19 is the potential to transmit either mother to fetus or mother/caregiver to neonates. However, neonates born from infected mothers did not show significant clinical features. Pharyngeal-swab, amniotic-fluid, cord-blood, and breast-milk test results were not found positive. Health facility-based vaginal/caesarian delivery was considered a low risk of transmission. However, recommended to separate neonates with infected mothers/caregivers and test immediately after birth to avoid the possible transmission. Mothers/caregivers should take routine preventive measures such as washing hands frequently and avoiding contact with infected people. If neonates suffered from the server acute respiratory distress requires intensive care urgently. Despite the possibility of the intrauterine transmission of COVID-19 direct evidence is still lacking so it needs more studies for further confirmation. The International Pediatric Association suggested preventive programs, curative care, vaccination, and telemedicine care as the minimum services and called on its members to address these cares during the pandemic.